Beyond the economic uncertainty of disease. - Eduardo Bejarano-Daza, Javier (Revista Facultad de Medicina de la Universidad Nacional de Colombia)
The complexity of healthcare insurance market regulation —derived from the presence of monopolies in the provision of services, externalities and other flaws inherent to asymmetric information such as moral hazard, risk selection, and adverse selection— is a phenomenon found in the Colombian healthcare system that causes persistent problems of inefficiency in the management and allocation of healthcare resources, which, in turn, generates a reduction in the supply of healthcare services in the country and affects the Colombian population's access to these services. Therefore, these problems are structural to the Colombian healthcare system and need to be analyzed to determine whether greater State intervention is needed to the point of suppressing private intermediaries (Health Promoting Entities), despite the large number of norms that currently regulate the health sector. Considering the above, the objective of this article was to analyze the failures of the Colombian health market, making a distinction between different healthcare complexity levels and taking into account the current postulates on the failures of the health market and their effects.